THE ROLE OF INTERNAL AUDIT IN RISK MANAGEMENT OF CORPORATE ORGANIZATIONS - Endang Susilawati; Vini Rizqi; Vina Permata Sari (Accounting Research Journal, 2023)
Abstract. The role of audit in a company is very important because auditis a control of all activities in the organization, so the function of internalaudit is to control all activities in the organization so that workimplementation is more effective and efficient according topredetermined standards, therefore the role of internal audit Thecompany's risk will be small because company risk management canhelp the company's risk of events that will be faced in the future. Thisresearch uses a qualitative approach which aims to understand thephenomena that occur in research subjects to assess research questionsand to provide data. based on the researchers' ideas. focuses on previousresearch findings regarding the role of internal auditors in implementinggood risk management for good corporate governance. Based on thedescription, analysis, data interpretation and statistical data processingthat have been described in the previous chapters, it can be concludedthat the level of effectiveness of the role of the internal audit function isimportant in operational risk management. Based on the calculationresults of the average level of effectiveness located in quadrant II in theCartesian Diagram, it shows that the role of the internal audit function inoperational risk management has been effective. The role of internalauditors in risk management is closely related to the risk managementsystem development stage. Top management must be aware of theirspecific functions and responsibilities in risk management. Topmanagement must provide appropriate signals to lower levels ofmanagement (top-down approach) to convince them of their operationalresponsibilities regarding for example the development andimplementation of internal controls. Keywords: Internal Audit, Risk Management